Israel a high-tech haven. - Kaplan, G.
The author describes how a well-developed military electronics technology, strong governmental support for industrial R&D and an influx of scientific talent from the USSR have endowed Israel with the wherewithal for thriving high-technology industries. He details how the small country has already begun to make its mark in global high-tech commerce
Keywords: Israel; Global high-tech commerce; Governmental support; High-technology industries; Industrial R&D.; Military electronics technology; Scientific talent